The Systematic Construction of Emergency Medical Security System in Long-Distance Walking Movement on Urban Paved Roads - Dong Jing; Yang Zheng; Ruan Jialong; Chen Jianing; Song Xiaohong (International Journal of Medical Science and Clinical Research Studies, 2024)
Objective To explore the scope of building emergency medical security mechanism in urban paved road environment, and to provide reference, sample data and improvement suggestions for building emergency medical security mechanism in such specific environment. Methods The data of rescue personnel deployment, rescue materials allocation, rescue force monitoring, actual rescue situation, emergency plan and relevant regulations setting, training and other aspects of the emergency medical security mechanism in March and April 2023 were collected, and the data were analyzed. Results (1) The hiking distance was 40km and the road conditions were urban paved roads. There were 1150 official trekkers and 65 people were treated medically. (2) The most common symptoms of outdoor hiking included skeletal muscle injury (19.48%), foot skin and soft tissue injury (18.17%), fever (2.61%) and diarrhea (0.61%). (3) In March, 18.36% of the core medical team members and 20.41% of the first aid volunteers who underwent systematic training took up the task of supporting hiking activities. In April, the core medical team personnel who undertook the task of supporting hiking activities accounted for 1.23% of the total number of the security team, and the first aid volunteers who underwent systematic training accounted for 37.04%. (4) According to local conditions, the multi-vehicle rescue and transport mode was adopted, which was combined with the modified commercial rescue vehicle (42.86%) with the on-board emergency medical unit (EMU) and the ordinary ambulance (28.57%). (5) More than 700 pieces of 34 kinds of medical materials and 40 sets of mobile communication equipment, which were put into use after the feasibility study of the expert group and the technical group, guaranteed the competition from the hardware level. Conclusion The construction of emergency medical support mechanism in outdoor walking sports needs to pay attention to environmental characteristics, operation mode of support team, personnel and adaptability training, equipment and deployment of medical support materials, deployment and cooperation of communication and transport capacity, reasonable support plan and other factors. Medical volunteers who have been systematically trained can undertake part of outdoor medical rescue work. Pre-activity training and regular re-training of medical volunteers can ensure the safety of outdoor activities.